Cateterização venosa: assistência de enfermagem-uti pediátrica - Oliveira, Maria Ivoneide Veríssimo de (2008)
This study has a descriptive nature and aims to describe the nursing assistance experienced by the nurses in the Peripheral Vein Catheterization at a pediatric intensive therapy unity in Fortaleza-Ce. The results showed that 100% of the nurses have as first precaution the conditions of the child’s vein system; 75% infused solution identification; 50% physical conditions observation; 38% therapy permanence time. At the complication time: 63% remove the appliance; 50% prefer to call the physician on duty; 25% observe infection signals and inform the physician on duty; 50% believe it is an insufficient number for assistance; 13% still develop bureaucratic functions. In this situation 50% of them assign responsibilities to nursing auxiliaries and technicians. Thus, it is concluded that the nurses are supposed to have direct action, because a technical ability of this process requires knowledge, and ability. The nurse must reconsider the professional practice; seek the duty sedimentation to care and control as not dissociable from the nursing responsibility.